Urbanization level and its effect on the structure and function of homegarden (pekarangan) vegetation in West Java, Indonesia - Muhammad Saddam Ali; Hadi Susilo Arifin; NURHAYATI NURHAYATI (Society for Indonesian Biodiversity, 2021)
Abstract. Ali MS, Arifin HS, Nurhayati. 2021. Urbanization level and its effect on the structure and function of homegarden (pekarangan) vegetation in West Java, Indonesia. Biodiversitas 22: 173-183. Urbanization occurs in West Java Province, Indonesia is currently reducing the ecological value of Indonesian pekarangan or homegardens by decreasing the average area of ??homegarden and the diversity and abundance of vegetation in them. One study site was in Bogor District, i.e. Selahuni 2, Ciomas Rahayu Village. Four sites in Bogor City, i.e. Sirnagalih-Pagentongan in Loji Village, Tegal Gundil Lama and Tegal Gundil Baru settlements in Tegal Gundil Village, and Baranangsiang Indah Settlement in Katulampa Village. One study site in Cianjur District, i.e. Cibakung Hamlet in Selajambe Village. The objective of this paper is to show the level of urbanization in each area of studies analyzed by Principle Component Analysis (PCA) and the dynamics of homegarden vegetation by comparing data from 1998, 2007, and 2019. The results showed that the levels of urbanization in the six study sites were moderately urbanized and highly urbanized. Homegarden dynamics occurred in the direction of changing homegarden area and the number of species and individuals of plants there. The dynamics of the homegarden due to urbanization have increased the composition of non-ornamental species, mostly fruit plants in all research sites in 2019.